HOW EFFECTIVE IS THE CODE OF ETHICS IN STRENGTHENING THE ROLE OF FORENSIC ACCOUNTING AND WHISTLEBLOWING IN PREVENTING FRAUDULENT FINANCIAL REPORTING? - Grace Lidya Romaito Hutagaol (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze factors that can influence financial statement fraud. The independent variables in the study are forensic accounting and whistleblowing with the code of ethics as a moderating factor. The study was conducted using a quantitative survey method with 100 employees working in the accounting, audit, and finance departments in both the public and private sectors in Indonesia and analyzed using SPSS. The results show that whistleblowing has an effect on financial statement fraud, including in a moderating relationship. Forensic accounting has an effect on financial statement fraud but not in a moderating relationship.